2007
DOI: 10.5194/cp-3-65-2007
|View full text |Cite
|
Sign up to set email alerts
|

On the variability of return periods of European winter precipitation extremes over the last three centuries

Abstract: Abstract.We investigate the changes of extreme European winter (December-February) precipitation back to 1700 and show for various European regions that return periods of extremely wet and dry winters are subject to significant changes both before and after the onset of anthropogenic influences. Generally, winter precipitation has become more extreme. We also examine the spatial pattern of the changes of the extremes covering the last 300 years where data quality is sufficient. Over central and Eastern Europe … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 48 publications
4
33
0
Order By: Relevance
“…This finding is in line with other studies that have detected a shift towards increased winter precipitation and the responsible circulation patterns in Central Europe (e.g. Caspary, 1995Caspary, , 2000Jacobeit et al, 2003Jacobeit et al, , 2006Belz et al, 2007;Pauling and Paeth, 2007;Petrow et al, 2007). …”
Section: Discussionsupporting
confidence: 82%
“…This finding is in line with other studies that have detected a shift towards increased winter precipitation and the responsible circulation patterns in Central Europe (e.g. Caspary, 1995Caspary, , 2000Jacobeit et al, 2003Jacobeit et al, , 2006Belz et al, 2007;Pauling and Paeth, 2007;Petrow et al, 2007). …”
Section: Discussionsupporting
confidence: 82%
“…During the first half of the Spörer Minimum, several catastrophic floods occurred in Switzerland in the 1470s and 1480s (Rötlisberger, 1991). Camuffo and Enzi (1995) found little if any relationship between solar activity and the flood frequencies of the Po, Tiber and Adige rivers in Italy during the past 2000 years including the Wolf and Spörer Minima and Pauling and Paeth (2007) found no clear connection between winter precipitation extremes in Central Europe and solar, volcanic or anthropogenic forcing.…”
Section: Can We Explain the Fluctuations In Observed Flood Frequency?mentioning
confidence: 99%
“…In our study, historical floods were compiled from the WSL historical and recent flood damage databases (Hilker et al, 2009;Rötlisberger, 1991), the Weikinn compilation (Weikinn, 1958(Weikinn, to 2002 and data from Gees (1997), Hächler (1991), Pfister (1984Pfister ( , 1998 and Schaub et al (1990). For the time period after 1500, the historical data was sufficient to include 14 catchments into the analysis.…”
Section: Historical Data Used and Study Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, increases in frequency and duration of west and north-west circulation patterns were observed (Werner et al, 2008). Pauling and Paeth (2007) identified an increase in extreme winter precipitation during the last 300 years over Europe. Casty et al (2005) found a close correlation between the NAO index and temperature and precipitation indices in the European Alps during the last 500 years.…”
Section: Introductionmentioning
confidence: 99%